Rademacher Complexity in Simplex/l∞ Set. Issue 1 (March 2021) - Lu, Yuwei
Abstract: When the size of the neural network is too large, calculating the bound of neural network is a difficult problem. Therefore, "size-independent" is what needs to look for here. This paper follows the path of "Size-Independent Sample Complexity of Neural Network ", and tries to get a better expression of Rademacher Complexity of neural networks.